Major non-odontogenic tumors found in childhood (Research, Society and Development, 2022)
Pediatric maxillary and mandibular tumors encompass a wide range of causes, histopathologies and clinical behaviors. Although many benign lesions are asymptomatic and discovered only on a routine dental radiograph, locally aggressive lesions and malignancies can cause pain, facial swelling, and trismus radiographic examination. In this context, the objective of this literature review is to describe the main non-odontogenic tumor alterations that can be found in the oral cavity of children, in order to help pediatric dentists in the diagnosis and establishment of appropriate treatment. For the construction of this work, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. From the review of selected articles on the subject, it was concluded that most tumors found in the oral cavity of children are benign and that surgical removal has been the main means of treating these lesions. Thus, it is important to emphasize the importance of a correct diagnosis in order to assess the type, size and extent of these lesions, as well as the risks caused during treatment, even before any procedure is performed.